Charge transport mechanisms and memory effects in amorphous TaN(x) thin films - Spyropoulos-Antonakakis, Nikolaos (Springer, 2013)
Amorphous semiconducting materials have unique electrical properties that may be beneficial in nanoelectronics, such as low leakage current, charge memory effects, and hysteresis functionality. However, electrical characteristics between different or neighboring regions in the same amorphous nanostructure may differ greatly. In this work, the bulk and surface local charge carrier transport properties of a-TaN(x) amorphous thin films deposited in two different substrates are investigated by conductive atomic force microscopy. The nitride films are grown either on Au (100) or Si [100] substrates by pulsed laser deposition at 157 nm in nitrogen environment. For the a-TaN(x) films deposited on Au, it is found that they display a negligible leakage current until a high bias voltage is reached. On the contrary, a much lower threshold voltage for the leakage current and a lower total resistance is observed for the a-TaN(x) film deposited on the Si substrate. Furthermore, I-V characteristics of the a-TaN(x) film deposited on Au show significant hysteresis effects for both polarities of bias voltage, while for the film deposited on Si hysteresis, effects appear only for positive bias voltage, suggesting that with the usage of the appropriate substrate, the a-TaN(x) nanodomains may have potential use as charge memory devices.